1990
DOI: 10.1302/0301-620x.72b6.2246284
|View full text |Cite
|
Sign up to set email alerts
|

Intra-osseous pressure and oxygen tension in avascular necrosis and osteoarthritis of the hip

Abstract: The intra-osseous pressure, P02, and PCO2 were measured in 32 hips (21 patients) which were painful but showed no severe degenerative changes. Pre-operative scintigraphy and radiography was performed in all patients. Thirteen hips showed early osteoarthritis, eight had early osteonecrosis, and 11 had no changes. Core biopsies were performed and the bone was examined histologically and graded for necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 15 publications
2
35
0
1
Order By: Relevance
“…Using a mass spectrometer, KIAER et al 6 likewise measured invasively after surgical exposure. They introduced two measurement probes transcutaneously during a surgical procedure on the head of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…Using a mass spectrometer, KIAER et al 6 likewise measured invasively after surgical exposure. They introduced two measurement probes transcutaneously during a surgical procedure on the head of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…A subchondral fracture is also present (reprinted with permission from Wolters Kluwer/LWW) inferior metaphyseal arteries [13]. Using direct measurements and computer simulations, a decrease in blood flow of 1.6 would be expected to reduce the intraosseous pO 2 from 75 to 50 mmHg, assuming a constant oxygen consumption rate, resulting in marked ischemia [14]. A unifying concept of the pathogenesis of ON has been presented that emphasizes the central role of vascular pathology and ischemia leading to osteocyte necrosis (Fig.…”
Section: Compromised Circulationmentioning
confidence: 99%
“…However, other observers have not found elevated intraosseous pressure measurements to be reproducible, specific, or sensitive [19][20][21]. One study suggested that the diagnostic sensitivity of the test in ON is low with 17 % of hips with ON having intraosseous pressures below 30 mmHg [14]. Another study found pressures to be below 30 mmHg in 32 % of hips with ON and concluded that this stress test lacks sufficient precision as a clinical diagnostic tool [21].…”
Section: Intraosseous Hypertensionmentioning
confidence: 99%
“…This finding could explain the increased intraosseous pulsatile pressure, the decreased microvascular blood flow and the decreased partial pressure of oxygen that has been found in femoral heads with ON [20,23].…”
Section: Pathogenesismentioning
confidence: 90%